Users' satisfaction and usability issues of students' attendance system application: UiTM here 1.0 / Adib Sarkawi ... [at al.] - Sarkawi, Adib; Johari, Aiza; Chachil, Ketty; Othman, Muhammad Fikri (Universiti Teknologi MARA, Sabah, 2022)
The way educators teach has changed, and so does the method of taking attendance. Due to the global pandemic situation, and the implementation of lockdown and social distancing, e-learning has taken over the regular learning process in most learning institutions. As a result, students’ attendance-taking needs to be conducted electronically. As manual attendance taking and absenteeism reporting classes are no longer seen as relevant in most circumstances, many learning institutions have developed various methods to take the students’ attendance effectively. In this university, the system developers have created a system application called UiTM Here 1.0, which aims to aid the process of taking the students’ attendance and absence reporting online. To take the attendance, the students will scan a QR code, and the system will take note of the date and time of the students clocking in and their absenteeism, based on the students’ ID. This user-friendly application is installed on the lecturers’ and students’ smartphones, where both parties can monitor the attendance. It can calculate the percentage of absence automatically and generate absence status immediately for each student. These records are sent automatically to the Students’ Academic Affairs Department. The present study emphasizes the system’s usability and the students’ satisfaction when using this application and it involves six research questions, in which an adopted online survey was distributed to 320 students (randomly shared). The results can be used to improve the system and notably, positive responses and a few constructive recommendations are revealed.